2020
DOI: 10.2478/ceer-2020-0026
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Adherence of Mortars Using Ultrasound

Abstract: Mortars are subjected to severe external stresses such as freezing, thawing, and drying during their lifetime. These stresses can lead to a loss of adhesion between the support and the mortar. The strength of the substrates with respect to their ability to receive a coating (mortar) is characterized in particular by the value of minimum tear resistance of the surface to be coated. In this work, the use of a non-destructive method which is both fast and easy to implement is employed to evaluate this support-mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
1
Order By: Relevance
“…The other two mortars have smaller increases ranging from 8% to 67%. These results contradict the results obtained by Khaldi et al [14]. The authors indicated a decrease in the adhesion of mortars with an increasing thickness.…”
Section: Effect Of Thicknesscontrasting
confidence: 87%
“…The other two mortars have smaller increases ranging from 8% to 67%. These results contradict the results obtained by Khaldi et al [14]. The authors indicated a decrease in the adhesion of mortars with an increasing thickness.…”
Section: Effect Of Thicknesscontrasting
confidence: 87%
“…When (y 0 − y 2 ) 2 takes the minimum value, the mortar strength can be calculated through the strength contour line of the functional relationship between the polymer-cement ratio and Formulas (2) and (3). By inferring and calculating the ratio of the correlation coefficient of the values, if the ratio of the two values is 0.9, it means that the correlation is better [22].…”
Section: Calculation Of Bond Mortar Strengthmentioning
confidence: 99%